The Consequences of Chorioamnionitis: Preterm Birth and Effects on Development - Robert Galinsky; Graeme R. Polglase; Stuart B. Hooper; M. Jane Black; Timothy J. M. Moss (Hindawi Limited, 2013)
Preterm birth is a major cause of perinatal mortality and long-term morbidity. Chorioamnionitis is a common cause of preterm birth. Clinical chorioamnionitis, characterised by maternal fever, leukocytosis, tachycardia, uterine tenderness, and preterm rupture of membranes, is less common than subclinical/histologic chorioamnionitis, which is asymptomatic and defined by inflammation of the chorion, amnion, and placenta. Chorioamnionitis is often associated with a fetal inflammatory response. The fetal inflammatory response syndrome (FIRS) is defined by increased systemic inflammatory cytokine concentrations, funisitis, and fetal vasculitis. Clinical and epidemiological studies have demonstrated that FIRS leads to poor cardiorespiratory, neurological, and renal outcomes. These observations are further supported by experimental studies that have improved our understanding of the mechanisms responsible for these outcomes. This paper outlines clinical and experimental studies that have improved our current understanding of the mechanisms responsible for chorioamnionitis-induced preterm birth and explores the cellular and physiological mechanisms underlying poor cardiorespiratory, neural, retinal, and renal outcomes observed in preterm infants exposed to chorioamnionitis.